Mastoparans: A Group of Multifunctional α-Helical Peptides With Promising Therapeutic Properties - de Santana, Carlos José Correia; Pires Júnior, Osmindo Rodrigues; Fontes, Wagner; Palma, Mário Sérgio [UNESP]; Castro, Mariana S. (Frontiers, 2022)
Biologically active peptides have been attracting increasing attention, whether to improve the understanding of their mechanisms of action or in the search for new therapeutic drugs. Wasp venoms have been explored as a remarkable source for these molecules. In this review, the main findings on the group of wasp linear cationic α-helical peptides called mastoparans were discussed. These compounds have a wide variety of biological effects, including mast cell degranulation, activation of protein G, phospholipase A2, C, and D activation, serotonin and insulin release, and antimicrobial, hemolytic, and anticancer activities, which could lead to the development of new therapeutic agents.
Keywords: antimicrobial peptide; linear cationic α-helical peptide; mast cell degranulation; mastoparans; social and solitary wasps; venom